New Earth - Bova, Ben, 1932-2020 (Tor, 2013)
"Award-winning author Ben Bova brings us New Earth, his latest tale of science fiction. The entire world is thrilled by the discovery of a new Earthlike planet. Advance imaging shows that the planet has oceans of liquid water and a breathable oxygen-rich atmosphere. Eager to gain more information, a human exploration team is soon dispatched to explore the planet, now nicknamed New Earth. All of the explorers understand that they are essentially on a one-way mission. The trip takes eighty years each way, so even if they are able to get back to Earth, nearly 200 years will have elapsed. They will have aged only a dozen years thanks to cryonic suspension, but their friends and family will be gone and the very society that they once knew will have changed beyond recognition. The explorers are going into exile, and they know it. They are on this mission not because they were the best available, but because they were expendable. Upon landing on the planet they discover something unexpected: New Earth is inhabited by a small group of intelligent creatures who look very much like human beings. Who are these people? Are they native to this world, or invaders from elsewhere?While they may seem inordinately friendly to the human explorers, what are their real motivations? What do they want?Moreover, the scientists begin to realize that this planet cannot possibly be natural. They face a startling and nearly unthinkable question: Could New Earth be an artifact?"--